Pengembangan Video Pembelajaran Animasi Berbasis STEM untuk Meningkatkan Keterampilan Berpikir Kritis dan Kemandirian Belajar - Mamonto, Siti Wulandari; Prasetyo, Zuhdan Kun; Sugara, Ujang; Jacobus, Susan N. H. (Jurnal Pendidikan Indonesia, 2024)
This research is motivated by the low critical thinking ability and learning independence of elementary school students. This research aims to develop STEM-based animation learning videos that are feasible, practical, and effective in improving these two aspects. The research uses a research and development (R&D) method with a 4D development model consisting of the stages of define, design, develop, and disseminate according to the Thiagarajan model. The subject of this study involves elementary school students as the main users. Data collection is carried out through feasibility tests, practicality, and effectiveness by involving material experts, media experts, teachers, and students. Data analysis uses independent t test and MANOVA for effectiveness. The results of the study showed that the learning videos developed were considered feasible by material experts (91.7) and media experts (80). The effectiveness of the product can be seen from the results of the independent t test and MANOVA with a significance of 0.000. The practicality of the video was rated high by teachers (88) and students (92.8), with a 100% implementation rate. The conclusion of this study is that STEM-based animation learning videos are able to significantly improve the critical thinking ability and learning independence of elementary school students, so that it can be implicated in learning.